Bio-inspired benign synthesis of Cr doped ZnO nanoparticles towards electrochemical detection of Bovine Serum Albumin - Vijayakumar D Jangannanavar; Hanumantagouda Basavanagoudra; Mallikarjun K Patil; Sanjeev R Inamdar; Husenappa Vaddar; Kotresh M Goudar (Chemical Physics Impact, 2023)
In this study, we aimed to synthesize monodisperse chromium-doped zinc oxide (Cr-ZnO) nanoparticles (NPs) through green synthesis for the construction of a highly sensitive electrochemical biosensor for BSA detection. Characterization techniques such as X-ray diffraction, FTIR spectroscopy, UV-Vis absorption, and photoluminescence studies confirmed the structural, chemical, and optical properties of the synthesized NPs. FESEM and EDS analysis revealed a spherical nodular morphology with a cauliflower-shaped structure. Nano-bio interaction studies between Cr-ZnO NPs and BSA were conducted using UV-Vis absorption and PL measurements, indicating fluorescence quenching due to complex formation. The synthesized NPs were utilized as electrode material for an electrochemical sensor, demonstrating sensitivity and selectivity in detecting BSA concentrations within the range of 1.5 nM to 48 nM. The sensor's response was linear, showing a decrease in anodic peak current response from 5.08 µA to 3.48 µA for different BSA concentrations. Remarkably, the optical interaction results mirrored the electrochemical findings, emphasizing the consistency between the two methods. The linear response of the electrochemical sensor, coupled with its optical interactions, suggests the versatility and reliability of the synthesized NPs for biosensing applications. With a simple setup requiring minimal samples, the electrochemical sensor offers an inexpensive, rapid, and sensitive screening method for BSA. These findings underscore the potential of the synthesized NPs as a promising electrochemical surface for biosensors, with implications for diagnostic and therapeutic applications, particularly in the context of cattle-related research.